Factors affecting Co-Creation Intention of Customers in Social Commerce - Klemens Wedanaji Prasastyo; Ian Nurpatria Suryawan; Fauzia Shabrina (Quantitative Economics and Management Studies, 2023)
This paper investigates the effects of social support, social commerce information sharing, and social commerce value on brand engagement and the effect of brand engagement on co-creation intention. This paper also investigates the mediating role of brand engagement on the relation between social support, social commerce information sharing, social commerce value and co-creation intention. The study used survey data from 279 Indonesians with experience using social commerce sites and make purchase transactions through social media sites. The model was tested using PLS structural equation modelling with WarpPLS 8.0 program. The empirical findings indicate that social support, social commerce information sharing, and social commerce value has a significant direct effect on brand engagement. The study also revealed that brand engagement has a significant direct effect on co-creation intention. The mediation test results indicate that brand engagement does not mediate social support, social commerce information sharing, and social commerce value on co-creation intention. This study provides an understanding that co-creation intention has become a common feature within the social commerce context and managers should make efforts to effectively engage with customers by implementing the relevant social commerce feature.